A313 INTRAGASTRIC BALLOON REMOVAL: PUNCTURE, DILATE, DEFLATE. (1st March 2018) - Falk, V; Eccles, J K; Karmali, S; Sultanian, R
Abstract: Background: The growing obesity epidemic has led to the development of a number of endoscopic bariatric weight-loss procedures, including intragastric balloons (IGB). The US FDA-approved IGB devices are the Orbera (Apollo Endosurgery), ReShape (ReShape Medical Inc), and Obalon (Obalon Therapeutics Inc), whilst two other internationally recognized IGB systems are the Spatz (Spatz Medical) and the Elipse (Allurion Technologies). Each device is made of silicone and filled with 0.9% saline solution to a total volume between 400-950cc. As per FDA approval, the IGB should be removed after 6 months. The most common side effects are nausea/vomiting, abdominal pain, and reflux, requiring early IGB removal in up to 9% of patients. Other complications include balloon deflation± migration, gastric ulcers, perforation, and pancreatitis. The mortality rate is 0.05%. Adverse events specific to removal of IGBs include aspiration pneumonia, esophageal tears and perforation. Although IGBs were CDFA-approved in Canada in the early 2000's, few endoscopists currently practice this procedure. Increasing international use of the IGB combined with the rising incidence of Canadians traveling abroad for bariatric procedures means that Canadian endoscopists will be faced with managing these devices and their complications. Aims: We describe the case of a patient who presented with complications due to IGB and detail our endoscopic approach to its safe removal. Methods: A 51-year-old male presented 14 months after IGB placement in Saudi Arabia with intractable reflux, nausea and vomitting. The balloon manufacturer was unknown. At ultrasonography, the IGB volume was 550cc. All laboratory investigations were normal. Results: The gastroscopy was performed under general anesthesia with endotracheal intubation. The IGB was identified and no significant complications noted within the stomach or esophagus. After an esophageal overtube was inserted, the wall of the IGB was punctured with an injector needle, but with poor drainage of fluid with aspiration alone. The puncture site allowed introduction of a JAG 0.035 wire into the balloon with subsequent dilatation of the opening by CRE balloon to 15mm and successful evacuation of fluid. Once decompressed, the balloon was grasped via snare and removed through the overtube. Repeat gastroscopy showed unharmed gastric and esophageal mucosa. The IGB was subsequently identified as a non-FDA/CDFA approved Spatz adjustable balloon (Image 1). Conclusions: The increased incidence of endoscopic bariatric interventions means that endoscopists will need to become familiar with management of IGBs and their complications. We recommend that IGBs be removed under general anesthesia using an esophageal overtube for safe extraction by following a "puncture, dilate and deflate" technique as described with an endoscopic assessment of gastric and esophageal mucosa post removal. Funding Agencies: CAG, None